2007
DOI: 10.1111/j.1365-2966.2007.12258.x
|View full text |Cite
|
Sign up to set email alerts
|

Type IIP supernova SN 2004et: a multiwavelength study in X-ray, optical and radio

Abstract: We present X‐ray, broad‐band optical and low‐frequency radio observations of the bright type IIP supernova SN 2004et. The Chandra X‐ray Observatory observed the supernova at three epochs, and the optical coverage spans a period of ∼470 d since explosion. The X‐ray emission softens with time, and we characterize the X‐ray luminosity evolution as LX∝t−0.4. We use the observed X‐ray luminosity to estimate a mass‐loss rate for the progenitor star of ∼2 × 10−6 M⊙ yr−1. The optical light curve shows a pronounced pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 36 publications
9
65
2
1
Order By: Relevance
“…They found that a star with an A less massive progenitor is expected if we use the wind density recovered for the SN 2004et pre-SN from X-ray observations. These data suggest the mass-loss rate of (2−2.5) × 10 −6 M yr −1 , assuming the wind velocity of 10 km s −1 (Rho et al 2007;Misra et al 2007). Using the RSG life-time of 7 × 10 5 yr for the 25 M main-sequence star (Hirshi et al 2004), we find the mass lost at the RSG phase to be ∼1.6 M with an uncertainty of ∼ ± 1 M .…”
Section: Progenitor Massmentioning
confidence: 96%
“…They found that a star with an A less massive progenitor is expected if we use the wind density recovered for the SN 2004et pre-SN from X-ray observations. These data suggest the mass-loss rate of (2−2.5) × 10 −6 M yr −1 , assuming the wind velocity of 10 km s −1 (Rho et al 2007;Misra et al 2007). Using the RSG life-time of 7 × 10 5 yr for the 25 M main-sequence star (Hirshi et al 2004), we find the mass lost at the RSG phase to be ∼1.6 M with an uncertainty of ∼ ± 1 M .…”
Section: Progenitor Massmentioning
confidence: 96%
“…Photometric and spectroscopic monitoring programs began in earnest soon thereafter. Results from optical monitoring are summarized by Sahu et al (2006) and Misra et al (2007).…”
Section: Sn 2004etmentioning
confidence: 99%
“…To explore this proposition further, we make use of the MIR photometry (see Table 1) and spectra (Figure 3), together with optical photometry (Sahu et al 2006;Misra et al 2007) and spectra (Sahu et al 2006).…”
Section: Evidence For Dustmentioning
confidence: 99%
“…Spectroscopic observations of SN 1999ga. The spectrum at 39.5 days is the one used to classify SN 1999ga (Salvo et al 1999 (Gezari et al 2009;Miller et al 2009), the type IIL SNe 1979C (Balinskaya et al 1980;de Vaucouleurs et al 1981;Barbon et al 1982b), 1980K (Barbon et al 1982aButa 1982;Tsvetkov 1983), 1990K (Cappellaro et al 1995b), 1994aj (Benetti et al 1998; the transitional type IIP/IIL SN 1992H (Clocchiatti et al 1996); the peculiar SN 1987A (Whitelock et al 1989, and references therein) and the type IIP SNe 2004et (Sahu et al 2006;Misra et al 2007) and 2005cs (Tsvetkov et al 2006;Pastorello et al 2006Pastorello et al , 2009. The explosion epochs of SNe IIL have been estimated to occur roughly 2−3 weeks before their maximum light (Patat et al 1993).…”
Section: Late Spectral Evolutionmentioning
confidence: 99%